ANALYSIS OF THE IMPLEMENTATION OF THE INFORMATION SYSTEM OF THE DILAMPUNG VILLAGE GOVERNMENT HALL (SINBAL) OF THE MINISTRY OF HOME AFFAIRS - Amelia Rahayu Safitri; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of the implementation of the Village Government Center Information System in Lampung, Ministry of Home Affairs. All data was obtained directly from informants in the field using interviews and document studies. The results of the study indicate that the implementation of the Village Government Center Information System in Lampung is a strategic effort by the Ministry of Home Affairs to support the digitalization of village governance. Based on the six dimensions of information system success, the implementation of the Village Government Center Information System in Lampung has not been fully optimal. The quality of the system and information still face technical and data accuracy challenges, service quality is not supported by adequate mentoring, and user satisfaction levels vary relatively due to differences in digital literacy among village officials.